Industrial alkyd resins: characterization of pentaerythritol and phthalic acid esters using integrated mass spectrometry. (23rd December 2014) - La Nasa, Jacopo; Degano, Ilaria; Modugno, Francesca; Colombini, Maria Perla
<x xml:space="preserve">Abstract</x> RATIONALE Alkyd resins are synthetic polyesters used as paints and coatings. Current approaches for their analysis do not allow the characterization of pentaerythritol and phthalic acid esters, whose detection is interesting to fully characterize the materials, e.g. for forensic or cultural heritage applications. METHODS A combined analytical approach based on Gas Chromatography/Mass Spectrometry (GC/MS), High‐Performance Liquid Chromatography (HPLC)/MS and flow injection analysis (FIA)/MS was adopted. GC/MS was used to characterize the fatty acid profile and the polybasic acids in extracts from industrial alkyd resins. HPLC/MS and FIA/MS were used for the characterization of the triglyceride profile of the oil used to manufacture the resin and for the identification of reaction products deriving from the synthesis process. RESULTS The multi‐analytical approach was applied on two different industrial alkyd resins produced from two different oils. The GC/MS analysis was successful in characterizing the fatty acid profile and the aromatic fraction of the resin. The HPLC/MS analysis allowed us to characterize the pentaerythritol and phthalic acid ester and the triglycerides residues from the synthesis process, by studying their high‐resolution tandem mass spectra. CONCLUSIONS The application of liquid chromatography coupled with high‐resolution tandem mass spectrometry to the study of industrial alkyd resins allowed us to characterize for the first time the esters formed by the transesterification reactions involving pentaerythritol, phthalic acid and triglycerides. Copyright © 2014 John Wiley & Sons, Ltd.